Implementasi Knowledge Management Pelestarian dan Pengembangan Seni dan Budaya Tradisional - Nurazza, Abdullah Fadli; Khilda, Amanda Amelia; Faris, Muhammad; Sugiarti, Yuni (Jurnal Manajemen Informatika JAMIKA, 2025)
The preservation and development of traditional arts and culture are vital to maintaining the cultural identity of a nation. However, with rapid advancements in technology and modern times, efforts to preserve traditional arts and culture face challenges in terms of information accessibility, documentation, and intergenerational collaboration. This research aims to develop a web-based knowledge management system as a solution for preserving and advancing traditional arts and culture in Indonesia. The system was developed using the Rapid Application Development (RAD) methodology, which enables rapid and responsive system development tailored to user needs. RAD consists of several key stages: requirements planning, prototype design, iterative construction, and final implementation, involving direct user feedback to incrementally refine the system. System evaluation was conducted using surveys and interviews to gather feedback from users. The primary features of the system include digital documentation, information access, and user discussion forums designed to enhance public understanding and awareness of traditional arts and culture. The results of this research demonstrate that the web-based system can serve as an effective solution for documenting, managing, and disseminating information related to traditional arts and culture. With this system, broader intergenerational collaboration is expected to be achieved, further strengthening the role of society in preserving traditional arts and culture as an invaluable heritage